The Philosophy of Karakalpak Folk National Games - Naubetulaeva Elmira (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
The role of Karakalpak folk national games in the intellectual development, physical health, and worldview of our ancestors has been discussed.